Consolidating and Accelerating Exports in Bangladesh - World Bank (World Bank, Dhaka, 2017)
Bangladesh sixth five year plan underscores the importance of exports for dynamism in the manufacturing sector and provision of high productivity and high income jobs. Indeed, faster export growth will be critical if Bangladesh is to achieve the accelerated growth necessary to reach its goal of becoming a middle income country by 2021. The focus of this study is to analyze the constraints to continued rapid growth in overall exports. This study seeks to focus on issues relating to i) continuation of fast growth in the basic garment sector; ii) providing an environment for encouraging export of mid and higher-value garments; iii) possibilities for diversification into IT-enabled services-business process outsourcing, or ITES-BPO; and iv) drawing some more general lessons for overall export growth.